HUBUNGAN KEMANDIRIAN BELAJAR DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH KALKULUS LANJUT - Ari Suningsih; Aulia Kesuma Putri (Eksponen, 2017)
The result of observation at STKIP Muhammadiyah Pringsewu Lampung in the last 5 academic year, it is found that the result of student learning in Advanced Calculus Course is still a lot of students who get the value of C, D and E is 397 (41,84%) students. This shows that the students' learning outcomes are still low. Allegedly low student learning outcomes due to the independence of learning. This is seen when given the task most students rarely do their own tasks. With regard to the matter then the formulation of the problem in this study is whether there is a relationship of independence learning and results learning outcomes in Advanced Calculus Courses, while the purpose of this study is to determine the relationship of learning independence and student learning outcomes. Sampling technique used in this research is Simple Random Sampling. To obtain data independence of student learning instrument used in the form of a questionnaire and to obtain data learning results using data documentation of learning outcomes. This research is a quantitative research with data analysis technique is Pearson Product Moment Correlation analysis. Based on data analysis, the result of the research shows that there is a strong correlation between student's learning independence on learning result in Advanced Calculus Course, this is indicated by the magnitude of correlation coefficient 0.566. This proves that learning independence contributes 32,04%.